Computational evaluation of hybrid method for car control and assignment problem in MCE systems - Minegishi, Tatsuya; Miyamoto, Toshiyuki (Conference proceedings - IEEE International Conference on Systems, Man, and Cybernetics, 2014)
As the height of buildings grows, the demand of enhancing transportation capability in buildings has been increasing. If many elevator shafts are installed, its footprint occupies most floor space; floor space for activities is reduced. Multi-car elevator (MCE) systems are studied as one of the solutions for this problem. MCE systems can increase transportation capability without increasing floor space because MCE systems have several cars in each shaft. Optimization of car control and call assignment is necessary to control MCE systems safety and transport passengers rapidly. Our previous studies formulated the optimization problem as an Integer Program (IP) and a Mixed Integer Program (MIP). There, however, is a problem on the time for optimization. Therefore, a hybrid method of Constraint Program (CP) and MIP is proposed in this paper and is evaluated through computational experiments. The results show that the proposed method can transport passengers faster than existing methods.